PARTISIPASI MASYARAKAT DALAM MITIGASI BENCANA BANJIR (Studi Kasus Sungai Wih Gile di Kampung Damaran Baru Kecamatan Timang Gajah Kabupaten Bener Meriah) - sakinah rahmah sakinah rahmah; Dr. Mahmuddin M,Si (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2019)
Participation is the willingness of the community to support government programs as well as the contribution of thinking power, energy in planning, implementing and maintaining the results of flood disaster mitigation. Damaran Baru is a chosen village as disaster prone. This study aims to determine community involvement in the implementation of flood disaster mitigation by accommodating community participation, then to find out the inhibiting factors that can influence community participation in flood disaster mitigation in the new Damaran village, Timang Gajah sub-qualitative approach. The sampling technique. Data pbtained through in-depeth interviews with informants who meet the criteria of research subjects. And provide relevant information needed in research. Form of participation of the new Damaran community can be seen from the government’s flagship flood mitigation planning program that of the three namely the introduction of detection devices and functions, flood disaster evacuation rehearsals and building commitments. Based on findings from the three programs the government is only this program that has just been implemented. The implementation of flood disaster mitigation has not yet proceeded properly, this can be seen from the lack of socialization and budget to carry out mitigation. Benefit taking, increasing community knowledge but this knowledge is not balanced with action. Those who receive the program as well as routine supervision. Participation inhibiting factors include communication, education, length of stay and employment. Keywords: Role, Participation, Flood, disaster Mitigation